Effect of Job Insecurity to Organizational Commitment and Intention to Leave - Cindy Sandra Lumingkewas; Umar Nimran; Kusdi Raharjo; Hamidah Nayati Utami (Wacana Journal of Social and Humanity Studies, 2019)
The purpose of this research was to test and to analyze the influence of job insecurity towards organizational commitment and the intention to leave especially for employees working in notary offices. This was caused by the very strategic position of such Notary employees especially in the process of deed writing, with what had been designed by the Notary, of course, would not be done along with the planning. The study was implemented in the province of DKI Jakarta, more precisely in Southern Jakarta. The number of samples was 191, taken using a multy-stage sampling technique. The result shows that job insecurity significantly influence the organizational commitment and the intention to leave, besides, the organizational commitment has become a partial mediation variable from the relationship channel between job insecurity and intention to leave. Such finding was along with the conservation of resources theory (COR theory), saying that employees try to collect and maintain many sources and if they lost their resources in one particular area, it would easily cause other loss of resources in other areas. When insecurity in working is sensed by employees, it would trigger the feeling of reluctant to work and intention to leave becomes higher. Therefore, the managerial implication is that the leader must focus on developing security towards employees within the notary office environment. When the employees are protected, the positive attitude would grow and they would gather and maintain such an attitude. Therefore, for future research, the commitment measurement using other source enables variable control related to the specific working context.